Impacts of carbon markets and subsidies on carbon capture and storage retrofitting of existing coal-fired units in China. (15th January 2023) - Li, Kaiyuan; Yang, Jin; Wei, Yanting
Abstract: Carbon capture and storage (CCS) is a feasible technology option to reduce carbon emission in the power industry. However, the high cost of CCS deployment in power plants precludes its large-scale application. Carbon markets may act as an incentive for CCS, but the impact of auction and quota allocation mechanisms in carbon markets on CCS is unclear. In order to investigate the roles of the auction and quota allocation mechanism on the CCS retrofitting in coal-fired units, the life-cycle cost method was used to evaluate the CCS retrofitting cost of China's coal-fired units in the carbon market after supplementing the existing database. The impact of subsidies on stimulating CCS retrofitting was jointly considered. The results show that most units have a CCS retrofit Levelized additional cost of electricity (Lacoe) of 25.24/MWh to 64.57/MWh, making the CCS retrofitting burdensome, even for ultra-supercritical unit that has a low cost. The combination of grandfathering quota allocation mechanism and subsidy will effectively promote CCS retrofitting of coal-fired units, especially when the auction ratio is 30%–40%, about 400–540 GW units will be retrofitted under the carbon market using grandfathering and 12.05/MWh-22.77/MWh subsidies. Additionally, there are significant differences among provinces in terms of the lifetime costs of the CCS retrofitting of coal-fired units. Xinjiang, Guangdong, and Jiangsu, with retrofitting potentials of respectively 20.68 GW, 10.58 GW–43.00 GW and 15.00 GW–52.27 GW are best suited for the CCS retrofitting of coal-fired units. Graphical abstract: Image 1 Highlights: Carbon capture and storage (CCS) retrofitting cost of coal-fired units was evaluated. Auctions and quota allocation mechanisms are considered cost factors. The impact of a combination of incentives on CCS retrofitting cost is explored. The auction ratio of 0%–40% with subsidy will encourage more units to be retrofitted. Regional differences make certain provinces better suited for the CCS retrofit.